Problem Solving Abilities of Malaysian University Students - Md.Yunus, Aida Suraya; Hamzah, Ramlah; Ahmad Tarmizi , Rohani; Abu, Rosini; Md.Nor, Sharifah; Ismail, Habsah; Wan Ali, Wan Zah; Abu Bakar, Kamariah (International Journal of Teaching and Learning in Higher Education, 2005)
Problem solving abilities of college graduates have received considerable attention among employers, university professors and the public at large. Problem solving is a generic skill that needs to be acquired in ensuring success in learning and in the workplace. This study focuses on problem solving abilities of Malaysian university students from the faculties of Engineering, Science, Computer Science, Medicine, Management and Law. A total of 3025 respondents participated in this study. Samples were chosen from seven public universities and two private universities. Data were collected using the Problem Solving Skills Scale (PSSS) component of the Social Problem Solving Inventory (SPSI). The SPSI consists of two major scales, Problem Orientation Scale (POS) and Problem Solving Skills Scale (PSSS). The purpose of this study was to describe the overall problem solving abilities of Malaysian university students, with comparisons made based on year of study and fields of study. There were significant difference between problem solving abilities of (a) final year and first year students, and (b) students from different fields of study.